The current rituality of Catholic death in Catalonia: A world of meanings. - Fons, Virginia (Death Studies, 2025)
This article sheds light on the current Catholic experience of mourning and death in Catalonia by means of theoretical-interpretative contributions from the field of rituality and the sensitive dimension. It focuses on a method of analysis that emphasizes the deep meanings and sensory dimension of the logic of the death ritual itself. Using multiple narratives and autoethnography, it describes the sequence of actions and sensations related to the drama experienced and channels the pain that is progressively expressed in the different phases of the ritual. The effectiveness of the ritual lies in the experience of non-presence, remoteness or emptiness. Even though the perspectives of the participants are different and there are a variety of family situations, the symbolic and sensitive dimension of the ritual works for everyone by sequencing their actions and experiences throughout the process.